On the Construction of Response Surface Designs with Minimum Level Changes - Varghese, Eldho; Bhowmik, Arpan; Jaggi, Seema; Varghese, Cini; Lall, Shwetank (Utilitas Mathematica, 2019)
It is often desirable to execute trials in response surface design (RSD) such that the number of input factor level changes is kept small and thus make the experiment cost-effective. This paper deals with the construction of RSDs with minimum level changes in the run sequences. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.